STIMULASI PELAYANAN PAP SMEAR MANDIRI MELALUI KEGIATAN TRAINING OF TRAINER TERHADAP BIDAN DESA DAN PEMERIKSAAN PAP SMEAR GRATIS - Winarti, Ni Wayan (Buletin Udayana Mengabdi, 2024)
Cervical cancer is the second most common cancer of women in Indonesia. One accurate early detection method for this cancer is pap smear. This examination is not yet available in Nusa Penida due to limitless of knowledge and skills of the health workers. Program Udayana Mengabdi was implemented in the form of Training of Trainers (TOT) to produce midwives who are competent in pap smear, and become source persons for their colleagues. The TOT was held on July 21, 2023 at Puskesmas Nusa Penida I with 10 midwives participating. They got lectures and did practice, with source persons and team from the Anatomical Pathology Specialist Study Program, Faculty of Medicine, Universitas Udayana. During the TOT, 35 women were given education about pap smear. After that, sampling practice was carried out by the midwives on these women, under the guidance of the team. In the next one month, the midwives sampled independently at their places of work. A total 84 samples were obtained and then evaluated by the team, and it was free of charge. It is hoped that this activity can stimulate independent and sustainable pap smear examinations in Nusa Penida. Keywords: Nusa Penida midwives, cervical cancer, Training of Trainer, pap smear